TANTANGAN DAN PELUANG PASAR MODAL DIERA DIGITAL DALAM MENINGKATKAN MINAT INVESTASI - Fadali Rahman; Mohammad Redy; Arini Nurfaizah; Nurinda Aulia Fikni; Alfin Naila; Enjang Tri Fauwas (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The digital revolution has fundamentally transformed the capital market paradigm, offering new opportunities and challenges in boosting investment interest. The capital market in the digital era provides ease of access, transaction efficiency, and financial inclusion, but also faces challenges such as low financial literacy, cybersecurity risks, and regulations that are not sufficiently adaptive to technological advancements. This article aims to explore the dynamics of the capital market in the digital era, analyze the challenges and opportunities faced by market participants, and suggest strategies to overcome existing barriers. It is expected that this article will provide insights for stakeholders in enhancing the attractiveness of Indonesia’s capital market and supporting sustainable national economic growth.